Dietary Chitosan Supplementation Increases Microbial Diversity and Attenuates the Severity of Citrobacter rodentium Infection in Mice - Guiping Guan; Hongbing Wang; Shuai Chen; Gang Liu; Xia Xiong; Bie Tan; Veeramuthu Duraipandiyan; Naif Abdullah Al-Dhabi; Jun Fang (Mediators of Inflammation)
C57BL/6 mice were tested in order to investigate the effects of dietary chitosan (COS) supplements on intestinal microflora and resistance to Citrobacter rodentium infection. The findings reveal that, after consuming a 300 mg/kg COS diet for 14 days, microflora became more diverse as a result of the supplement. Mice receiving COS exhibited an increase in the percentage of Bacteroidetes phylum and a decrease in the percentage of Firmicutes phylum. After Citrobacter rodentium infection, the histopathology scores indicated that COS feeding resulted in less severe colitis. IL-6 and TNF-α were significantly lower in colon from COS-feeding mice than those in the control group. Furthermore, mice in COS group were also found to experience inhibited activation of nuclear factor-kappa B (NF-κB) in the colonic tissue. Overall, the findings revealed that adding 300 mg/kg COS to the diet changed the composition of the intestinal microflora of mice, resulting in suppressed NF-κB activation and less production of TNF-α and IL-6; and these changes led to better control of inflammation and resolution of infection with C. rodentium.